Eyes on the horizon : historical constructions of international identity in Singapore, 1959-1999 - Chin, Li-Cheng (Nanyang Technological University, 2020)
This study examines how the Singaporean state has historically sought to construct and articulate to its citizenry an international identity, defined as ideas about the nation’s position vis-à-vis other nation-states or regions. It covers the period from 1959 to 1999, from Singapore’s self-governance until the decline of the Asian Values discourse; further developments in the twenty-first century are covered in the conclusion. Looking at the relationship between the three prominent ideas of regions which have figured in Singapore’s national narrative – the global, Asia and Southeast Asia, I argue that the Singaporean state has historically constructed a global-yet-Asian international identity which combines a sense of being global as predicated on leapfrogging the immediate region and an exclusively Confucian or East Asian definition of Asia. This global-yet-Asian identity thus distances the nation’s identity from Southeast Asia and reinforces the idea of the immediate region as Singapore’s ‘other’. It also addresses why Southeast Asia remains eclipsed by this global-yet-Asian identity despite increasingly figuring in the national narrative over the years. Overall, the study highlights that the historical global-yet-Asian identity presents an obstacle to deeper regional integration between Singapore and ASEAN and also showcases the importance of taking an international approach to national identity.